Prevalence and Metabolic Factors of Hyperuricemia in an Elderly Agricultural and Fishing Population in Taiwan - Qian YU,; Hsi-che SHEN,; Yi-chun HU,; Yu-fen CHEN,; Tao-hsin TUNG, (Archives of Rheumatology, 2017)
Objectives: This study aims to explore the potential condition-related sex differences to understand the overall pathogenesis of hyperuricemia among the elderly agricultural and fishing population in Taipei, Taiwan. Patients and methods: This study included 4,372 healthy elderly agricultural and fishing professionals (2,766 males, 1,606 females; mean age 74.4±6.6 years; range 65.0 to 90.3 years) voluntarily admitted to a teaching hospital in Taipei, Taiwan for physical exams in 2010. Their fasting blood samples were drawn through venipuncture, and they were administered a structured questionnaire by clinical nurses. Results: The overall prevalence of hyperuricemia was 30.4%, which increased significantly with increasing age (p<0.001). The prevalence was similar in males (30.2%) and females (30.6%) (p=0.78). Age, obesity, type 2 diabetes, hypercholesterolemia, hypertriglyceridemia as well as low high- density lipoprotein and high blood urea nitrogen, creatinine, and alanine amino transferase levels were significantly associated with hyperuricemia. Hypercholesterolemia (odds ratio [OR]=1.26, 95% confidence interval [CI]: 1.05-2.50) and high creatinine levels (OR=3.75, 95% CI: 2.64-5.33) were significantly associated with hyperuricemia in males, whereas type 2 diabetes (OR=1.54, 95% CI: 1.22–1.93) and high alanine amino transferase levels (OR=1.79, 95% CI: 1.31-2.43) were significantly associated with hyperuricemia in females. Hyperuricemia disparity among age groups was also revealed. Conclusion: Several sex-related differences with regard to factors including age, obesity, type 2 diabetes, hypercholesterolemia, hypertriglyceridemia, low high-density lipoprotein, high blood urea nitrogen, creatinine, and alanine amino transferase levels were indicated in the prevalence of hyperuricemia in this specific elderly population.